ANÁLISE DO CONTEÚDO DANÇA NAS PROPOSTAS CURRICULARES ESTADUAIS DE EDUCAÇÃO FÍSICA DO BRASIL - Diniz, Irlla Karla Dos Santos; Darido, Suraya Cristina [UNESP] (Universidade Estadual de Maringá, 2015)
This study aimed to analyze how the State Curriculum Proposals (SCP) for Physical Education approach the dance content in elementary school, trying to outline how this content is covered in these documents. In order to achieve this goal, it was developed a document review in 17 (SCP). Data was analyzed based on the perspective of thematic categories, which are: the indication or not of dance as a content of Physical Education and the identification of its theoretical framework; which are the terms used to describe dance; the existence or not of curricular organization proposals and classification of dance subtopics; and whereas the dimension of the contents (conceptual, procedural and attitudinal) were presented or not. The results suggested that dance is a relevant content to the SCP, since all of them proposed this theme on their guidelines. However, the objectives, the theoretical framework and the content dimensions presented some divergences between one another.

Este estudo teve como objetivo analisar como o conteúdo da dança é tratado nas Propostas Curriculares Estaduais (PCE) de Educação Física no Ensino Fundamental procurando delinear como o conteúdo é abordado nesses documentos. Para tanto, desenvolveu-se uma análise documental em 17 PCE. Os dados foram analisados a partir de categorias temáticas, sendo elas: a indicação ou não da dança como um conteúdo da Educação Física, e a identificação do referencial teórico; quais os termos empregados para designar a dança; a existência ou não de propostas de organização curricular e classificação dos subtemas da dança; e se as dimensões dos conteúdos (conceitual, procedimental e atitudinal) foram ou não apresentadas. Os resultados apontaram que a dança é um conteúdo relevante para as PCE, já que todas propuseram esse tema em suas diretrizes.Todavia, os objetivos, o referencial teórico e as dimensões dos conteúdos apresentaram divergências entre si.
ANALYSIS OF DANCE CONTENT ON STATE CURRICULUM PROPOSALS OF PHYSICAL EDUCATION IN BRAZIL
Keywords: Scholar physical education; Dance; State curriculum proposals; Educação física escolar; Dança; Propostas curriculares estaduais